Brand-Management Theoretical Principles in Music Business - Danilova, Kateryna; Krupa, Oksana (Socio-Cultural Management Journal, 2021)
Introduction. Today there are many music artists, and each creates a large amount of musical and visual content. But the modern consumer is increasingly critical of the content consumed. The task arises to convey the artist’s work to a wider audience, to create a strong loyal fanbase. This is the case when brand management is worth mentioning, which allows promoting the audience loyalty formation for a long time. Purpose and methods. The purpose of the article is to substantiate the theoretical foundations of brand management in the organization of the music business for increasing the music artists’ competitiveness and their promotion effectiveness in the music market. The system approach, methods of analysis, and synthesis, in particular, analysis of the literature about brand management, its effectiveness evaluation, and promotion of music artists are used. Results. The essence and significance of brand and brand management, features of brand management in the music business are revealed. Theoretical principles of brand management in increasing the competitiveness of music artists and their promotion effectiveness are considered. The main methods of evaluating the effectiveness of brand management are described. Conclusions. The scientific novelty of the article lies in offering to consider a music artist as a brand and promote it in the market according to the principles of brand management. It also proposes to transfer the methods of estimating the product brand building and promotion efficiency to the musician’s brand. The significance of the research lies in the possible use of its results in the integration of brand management into music artists’ promoting strategy in Ukraine, as well as in developing recommendations for the promoting strategy of Ukrainian show business music artists.